2021
DOI: 10.1158/1078-0432.ccr-20-4574
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid Cell–associated Resistance to PD-1/PD-L1 Blockade in Urothelial Cancer Revealed Through Bulk and Single-cell RNA Sequencing

Abstract: Purpose: To define dominant molecular and cellular features associated with PD-1/PD-L1 blockade resistance in metastatic urothelial cancer. Experimental Design: We pursued an unbiased approach using bulk RNA sequencing data from two clinical trials to discover (IMvigor 210) and validate (CheckMate 275) pretreatment molecular features associated with resistance to PD-1/PD-L1 blockade in metastatic urothelial cancer. We then ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 54 publications
2
34
1
Order By: Relevance
“…Conversely, CD169 + M1-like macrophages in the tumor-draining lymph nodes [48], but not in the tumor [25], are positively correlated with a favorable prognosis in MIBC patients. However, single-cell RNA-seq from immune-infiltrating cells revealed the wide diversity of TAMs in MIBC patients [49]. In this study, six different subsets of monocytes/macrophages were found in MIBC tumor, and their gene signatures did not correlate with the classical M1-like versus M2-like signatures.…”
Section: Association Of Macrophages Clinicopathological Features and Outcomes In Bladder Cancercontrasting
confidence: 55%
See 3 more Smart Citations
“…Conversely, CD169 + M1-like macrophages in the tumor-draining lymph nodes [48], but not in the tumor [25], are positively correlated with a favorable prognosis in MIBC patients. However, single-cell RNA-seq from immune-infiltrating cells revealed the wide diversity of TAMs in MIBC patients [49]. In this study, six different subsets of monocytes/macrophages were found in MIBC tumor, and their gene signatures did not correlate with the classical M1-like versus M2-like signatures.…”
Section: Association Of Macrophages Clinicopathological Features and Outcomes In Bladder Cancercontrasting
confidence: 55%
“…In this study, six different subsets of monocytes/macrophages were found in MIBC tumor, and their gene signatures did not correlate with the classical M1-like versus M2-like signatures. Moreover, the authors also identified another subset of TAM that shares both TAM-like and MDSC-like gene signatures [49], supporting the theory of the MDSC-to-macrophage differentiation. In the future, determining the origin of TAM (from tissue-resident macrophages, monocytes-derived macrophages or MDSC differentiation) could improve knowledge on TAM diversity and complexity but this is still limited by the lack of specific markers for each subtype.…”
Section: Association Of Macrophages Clinicopathological Features and Outcomes In Bladder Cancermentioning
confidence: 53%
See 2 more Smart Citations
“…Solid cancers are rarely composed of similar cells with identical epigenetic traits. Rather, non-genetic determinants diversify cell populations into distinct phenotypes or cell states with various degrees of metastatic potential and resistance to various therapies [ 43 , 44 ]. Specifically, phenotypic heterogeneity along the EMT spectrum, or EM plasticity (EMP), is emerging as a distinctive feature of primary tumors [ 45 ], CTCs [ 46 , 47 ], and in the relation between tumors and CTCs [ 48 ].…”
Section: Discussionmentioning
confidence: 99%